Combined squeeze-shear properties of magnetorheological fluids: Effect of pressure. (June 2014) - Spaggiari, Andrea; Dragoni, Eugenio
Several applications of magnetorheological fluids are nowadays present in the industrial world; however, sometimes material properties are not sufficient to meet the system requirements. Among the technical literature, there is experimental evidence of the squeeze-strengthen effect, which is a pressure dependency of the yield stress of the magnetorheological fluid. Since many magnetorheological systems are rotary devices, such as brakes and clutches, this article investigates the behaviour of magnetorheological fluids under pressure when a rotation is applied to shear the fluid. The system is designed to apply both the magnetic field and the pressure following a design of experiment method. The experimental apparatus comprises a cylinder in which a piston applies both pressure and a prescribed rotation. The magnetic circuit is designed to provide a tunable, nearly constant magnetic induction field inside the fluid. The experimental apparatus measures the torque produced by the magnetorheological fluid as a function of the variables considered, and consequently, the yield shear stress is evaluated. A statistical analysis of the results finds a positive interaction between the magnetic field and the pressure, which enhances the magnetorheological fluid performances, measured in terms of yield stress, up to more than two times the manufacturer's datasheet values.